2020
DOI: 10.1063/5.0033281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface morphological structure of a brown alga miyeok (Undaria pinnatifida) on sustainable drag reduction

Abstract: Liquid-infused surfaces are a promising passive technique for frictional drag reduction. However, their practical application is limited by the easy depletion of the lubricant infused in the surface by external forces. Miyeok contains mucus on its surface, which induces a sustainable slippery surface under flow conditions. In this study, the effect of the surface morphological structures of miyeok on slippery characteristics was examined. The surface of miyeok has bump-like microstructures and tiny pores of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…[ 134 ] Lee et al used a mixture of PDMS and curing agent to prepare positive and negative templates when copying the surface microstructure of Undaria pinnatifida and Laminaria japonica . [ 133 ] A double‐sided PDMS film for wound dressing was successfully prepared by Lin et al [ 22 ] The outer layer of the film perfectly reproduced the microstructure of shark skin. Yun et al fabricated surface microstructures of lotus leaves by replication molding with fresh lotus leaves, and the finished products had excellent hydrophobic properties.…”
Section: Fabrication Methods Of Bionic Microstructure Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…[ 134 ] Lee et al used a mixture of PDMS and curing agent to prepare positive and negative templates when copying the surface microstructure of Undaria pinnatifida and Laminaria japonica . [ 133 ] A double‐sided PDMS film for wound dressing was successfully prepared by Lin et al [ 22 ] The outer layer of the film perfectly reproduced the microstructure of shark skin. Yun et al fabricated surface microstructures of lotus leaves by replication molding with fresh lotus leaves, and the finished products had excellent hydrophobic properties.…”
Section: Fabrication Methods Of Bionic Microstructure Surfacementioning
confidence: 99%
“…The drag reduction effect of the test surface relative to the original surface can be determined by comparing the measured pressure drop. [ 133 ] Ahmmed et al conducted turbulence experiments in closed channels and measured the pressure drop of several test samples under different Reynolds numbers. [ 96 ] Li et al measured the longitudinal pressure drop in a turbulent channel to check the drag‐reducing ability of a microstructure surface coated with Cu 2 O particles.…”
Section: Experimental Methods For Measuring Drag Reductionmentioning
confidence: 99%
“…The obtained slippery surface demonstrated low ice adhesion strength when 100 cSt silicone oil was infused at or below 8% levels in the microtextured silicone material. Recently, inspired by the miyeok which contains mucus on its surface, Choi’s groups replicated its surface morphology using PDMS and then dipped into the silicone oil to obtain a slippery surface . The results indicated that the bump-like microstructure on the miyeok replica surface was beneficial to reduce the leakage of the lubricant.…”
Section: Fabrication Of Bioinspired Scalphobic Surfacesmentioning
confidence: 99%
“…Recently, inspired by the miyeok which contains mucus on its surface, Choi's groups replicated its surface morphology using PDMS and then dipped into the silicone oil to obtain a slippery surface. 71 The results indicated that the bump-like microstructure on the miyeok replica surface was beneficial to reduce the leakage of the lubricant. From these fabrication examples, the replication is environmentally friendly, easily manufactured on a large scale, and morphologically plastic.…”
Section: Surfacesmentioning
confidence: 99%
“…The surface of kelp has a uniformly distributed concave–convex microstructure, and its mucus has a good lubricating effect under high temperature and pressure. Lee et al (2020) fabricated a liquid-infused miyeok replica surface (LIMRS) using a liquid-infused surface technique, and the pressure drop and sliding length on the smooth surface indicated that LIMRS had a sustainable drag reduction effect. The exploration of natural plant mucilage, such as the discovery of fibrinolytic nattokinase in natto mucilage, the results of pins of PEEK were slid against a steel disk in a pin-on-disk tester showed that the aqueous with nattokinase reduced the coefficient of friction (COF) by 30% compared to dry friction and exhibited excellent lubricity (Minn and Sinha, 2012).…”
Section: Introductionmentioning
confidence: 99%